Protective role of diets containing Gongronema latifolium leaves on Streptozotocin- induced oxidative stress and liver damage - Henry Dan Akpan, Arit J Ekpo (Journal of Applied Pharmaceutical Science, 2015)
This study was aimed at determining some biomarkers of oxidative stress and liver damage in diabetic rats consuming diets containing Gongronema latifolium leaves so as to evaluate the involvement of the diets in the management of oxidative stress and liver damage common among diabetics. Fifty rats were randomly divided into five groups (1 to 5) with10 rats per group. Group 1 (normal control) consumed control diet; Group 2 (diabetic control) consumed control diet, Group 3 and 4 (diabetic treated) consumed Gongronema latifolium at 5% and 7.5%, respectively. Group 5 (diabetic treated) consumed control diet and was treated with Insulin. Feed and water were given ad- libitum for 28 days. Results showed that diabetic rats in groups 3 and 4 consuming Gongronema latifolium had significant (P
Keywords: Diet, Diabetes, Gongronema latifolium , oxidative stress, liver damage.